PENGARUH PENDIDIKAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU SMP DARUL MUMININ BEKASI - Fajri, Muflikhul (STKIP PGRI Bandar Lampung, 2019)
The success of the education process in order to produce quality Indonesian human resources, will be determined by many factors, including students, educators, curriculum, management of education and educational facilities. Learning outcomes are influenced by many very complex and complex factors. Because of the limited time, funds, and abilities, the authors limit this study to only three important problem factors that are considered the most decisive of teacher professionalism, namely the problem of teacher education and teaching experience. This research is only limited to the teacher because the teacher is the spearhead in learning activities. The quality of education is largely determined by the performance of the teacher even though other factors cannot be ignored. The method used in this study is a survey with correlational techniques. Teacher education has a positive influence on teacher professionalism which is characterized by the acquisition of determination coefficient (r2y1) = 0.932 which means that 93.2% occurs in the tendency of the influence of increasing teacher education (X1) on teacher professionalism. The remaining 6.8% is explained by other reasons. Teacher teaching experience has a positive and significant influence on teacher professionalism which is characterized by the acquisition of determination coefficient (r2y2) of = 0.805 which means that 80.5% that occurs in the large tendency of the influence of teacher teaching experience (X2) on teacher professionalism. The remaining 19.5% is explained by other reasons. Teacher education and teacher teaching experience together provide a positive and significant influence on teacher professionalism which is characterized by the acquisition of multiple determination coefficients (r2y12) = 0.932 which means that 93.2% occurs in the tendency of the increase in teacher education and teaching experience teacher towards teacher professionalism. The remaining 6.8% is explained by other reasons.